Development of Student Learning Programs with a Realistic Mathematic Education (RME) Approach to Improve Students' Critical Thinking Skills - Rudy Setiawan; Elita Mega Selvia Wijaya (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
This study aims to produce student worksheets with a Realistic Mathematic Education (RME) approach to solving valid, practical, and effective linear program problems. The development of this learning program is based on the Four-D Model adopted from Thiagarajan, Semmel, namely defining(define), design (design), and action (develop). The implementation of the criteria set by conducting validation and field trials. The learning tools developed are in the form of RPP and MFI. The subjects of the development trial were students of the mathematics education study program. Based on the results of data analysis, mathematics learning programs with a Realistic Mathematic Education (RME) approach can be applied and carried out correctly. This is shown from the results of the MFI trial with an average score of 83, which is included in the excellent category. In addition, the test questions test got an average score of 86.8, which also fell into the outstanding category. From this, it is known that the student learning program is ethical and practical for learning.